2005
DOI: 10.1001/jama.294.9.1172
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Patients

Abstract: S tandardized patients are trained actors who portray patients during an interview and physical examination with a medical student or doctor in training. As part of medical education, medical schools now often use standardized patients to depict realistic patient interactions and presentations of disease. These standardized patients discuss their symptoms with the student. The medical student in turn conducts a patient interview and then may perform a physical examination. Through these interviews, medical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
1
12
0
3
Order By: Relevance
“…Standardized patients (also referred to as simulated patients) are actors trained to simulate behaviors of real patients including physical and mental symptoms and problems. Standardized patients are widely used in medical education and research (Brender, Burke, and Glass 2005). Our findings with actual doctor-patient interactions provide further evidence of the usefulness of applying the SCT framework to doctor and patient encounters.…”
Section: Discussionsupporting
confidence: 56%
“…Standardized patients (also referred to as simulated patients) are actors trained to simulate behaviors of real patients including physical and mental symptoms and problems. Standardized patients are widely used in medical education and research (Brender, Burke, and Glass 2005). Our findings with actual doctor-patient interactions provide further evidence of the usefulness of applying the SCT framework to doctor and patient encounters.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, instructors can observe the interactions and evaluate the students' progress. 41,42 Koerber et al used SPs in training dental students in TCC and found that motivational interviewing increased patient involvement in counseling sessions. 29 Other studies have found that using SPs may 40,[42][43][44][45][46][47][48][49] or may not be cost-efficient.…”
mentioning
confidence: 99%
“…Yet, Glass, Brender and Burke (2005) and Robinson-Smith, Bradley and Meakim (2009) argue that SP are trained actors who portray patients. Nevertheless, Churchouse and McCafferty (2012) offer clarity and a structured approach to defining the difference.…”
Section: The Teaching Workhopmentioning
confidence: 99%